COVID-19 and Mental Health: The Emotional Impact of Social Distancing and Mediating Protective Factors - Dr. Maggie Parker; Stephanie F Dailey (OSF Registries, 2020)
The purpose of this study is to understand the psychosocial impact and mediating protective factors of social distancing measures during the COVID-19 pandemic to advance support structures for social distancing practices, guide public health recommendations, and inform mental health resource allocation and support services. This study has two specific aims, first to understand the psychological impact of social distancing measures on overall levels of mental health and second to assess the associations between psychological distress, social connectivity, well-being, awareness, resilience, and coping. Leveraging the disaster mental health literature, demographic questions will address risk and protective factors in an effort to better understand the impact of social distancing on high risk populations. Research findings are intended to inform: 1) mental health professionals in better understanding mental health needs and supportive practices (e.g., coping strategies, the role of resilience) for individuals and communities; 2) public health authorities in the generation of evidence-informed guidance related to mental health, planning community based supportive practices, and targeted resource allocation for mental health support services; and 3) nonprofits and public media outlets providing the general public with psycho-education on coping with COVID-19 and social distancing.
Keywords: Psychiatry and Psychology; Public Health; Medicine and Health Sciences; Counseling; Social Work; Mental and Social Health; Social and Behavioral Sciences; Psychology; Other Social and Behavioral Sciences; COVID-19; Coping; Mental Health; Resilience; Social Connectedness; Social Distancing